Edukasi “CERVIBOOK” (Cerita Video dan Booklet) terhadap Kemampuan Kognitif dan Sikap Orangtua tentang Pencegahan Stunting pada Balita (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Stunting is a disturbance of growth and development of children due to malnutrition. Stunting prevention can be done by parents, one of which is through cognitive abilities and attitudes. Cognitive abilities and attitudes of parents can be obtained through education from health workers. This study aims to determine the effect of educational "Cervibook" (video stories and booklets) on cognitive abilities and parents' attitudes about stunting prevention in toddlers. The research design used a pre-experiment with a one group pre and post test design approach. The study population consisted of 38 people and a sample of 34 respondents was obtained through the purposive sampling technique. Intervention was given 3 times for 1 week with a duration of ± 30 minutes of intervention. Measuring tool used is a questionnaire sheet. Data analysis using the Wilcoxon test. The results of the study showed that almost half (47.1%) of the pre-test cognitive abilities had adequate cognitive abilities and the post-test fully (100%) had good cognitive abilities. The pre-test attitude data were almost entirely (76.5%) in the category of negative attitudes and most of the post-test (70.6%) were in the positive attitude category. Based on the results of the Wilcoxon sign test (p value = 0.000) (α = 0.05) so that there is an effect of "Cervibook" Education (video stories and booklets) on cognitive abilities and attitudes of parents about stunting prevention in toddlers. Cervibook (video stories and booklets) is an interesting and unique form of counseling that can help parents more easily understand the information provided. It is recommended for parents to be able to apply "Cervibook" education independently by reading booklets or watching video stories on stunting prevention as an effort to increase knowledge